PERANAN ‘RELAWAN DEMOKRASI’ KOMISI PEMILIHAN UMUM DALAM PENYELENGGARAAN PEMILU TAHUN 2019 DI PROVINSI JAWA TENGAH - Theresia Bayu Ester K; Nur Hidayat - Sardini (Journal of Politic and Government Studies, 2022)
Indonesia’s voter participation rate in the General Election years ago tends to decrease. Because of this situation, the General Election Commissions of Indonesia create a program namely the Democratic Volunteers for every region in Indonesia. The Democratic Volunteers become the extensions of the hand of the General Election Commissions to educate and give socialization about the General Election that has the main purpose to increase the community participation in using their voting rights. The purpose of this research is to analyze the role of the Democratic Volunteers in the socialization of the 2019 simultaneous General Election in Salatiga and Brebes. This research uses the theory of political participation, political socialization, and volunteerism by using the descriptive qualitative method. The data collection was done by using in-depth interviews as the primary data and the secondary data obtained through study documentation reports. The result of the research shows that the Democratic Volunteers of the General Election Commissions in Salatiga and Brebes had done their role and duty to give the socialization of the voter education to the society. By applying several methods of socialization such as using media as equipment for the socialization and also setting socialization goals, to make these activities more attractive to educate the society. With good cooperation, the Democratic Volunteers activities for the General Election in 2019 have increased the voter participation rate in Salatiga and Brebes. There are several obstacles encountered by the Democratic Volunteer in socializing the 2019 simoltaneous General Election, but they are always trying their best and find solutions for the socialization activities that can go well in society